Environmental quality and social insurance - Eftichios Sophocles Sartzetakis; Panagiotis Demetrios Tsigaris (Fondazione Eni Enrico Mattei (FEEM), 1997)
This paper examines the double dividend hypothesis under wage uncertainty. In the presence of two market failures we show that second-best requires a lower than the Pigouvian tax, and a higher than "first-best" labour income tax. Starting from a state in which the environmental tax is below second best, we consider increasing it and at the same time recycle the additional revenues to reduce labour income tax. This revenue recycling policy has three effects: the positive Pigouvian effect, the negative tax interaction effect and the revenue recycling effect which is positive under certainty. In the presence of uncertainty, we find that the revenue recycling effect is negative if labour income tax is below second best, due to the social insurance effect. Our results have significant policy implications. First, environmental policies that do not generate revenue could be equally efficient to those that generate revenue. Second, revenues generated by environmental policies should not be used to decrease labour income taxes. We argue that environmental recycling policies can violate the uncontroversial, in the case of certainty, weak form double dividend hypothesis.
Keywords: H21; H23; D62; 330; Double dividend hypothesis; Environmental taxation; Labour income taxation; Wage uncertainty; Tax incidence analysis; Second best optimum; Optimale Besteuerung; Ökosteuer; Einkommensteuer; Theorie